2013
DOI: 10.1002/ccd.25232
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with the glidesheath slender for transradial coronary angiography and intervention: A feasibility study with prospective radial ultrasound follow‐up

Abstract: Routine use of the Glidesheath Slender for TR coronary angiography and interventions is safe and feasible with a high rate of procedural success and a low rate of RAO. © 2013 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 22 publications
(26 reference statements)
1
34
0
1
Order By: Relevance
“…This may relate to the lack of radial specific equipment and sheaths used in these studies that would increase RAS rates, particularly when using sheaths without hydrophilic coatings [37]. An additional factor is that many centers use smaller diameter 5Fr radial sheaths and catheters for diagnostic cardiac catheterization that would decrease rates of RAS observed as would use of more contemporary thinner wall sheaths such as the Glidesheath Slender which combines an inner diameter compatible with 6Fr guiding catheter with an outer diameter close to current 5Fr sheaths where RAS rates have been reported as low as 4.4% [38]. Finally sheathless guide catheter usage may also result in lower rates of RAS than those reported in the 'placebo'…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…This may relate to the lack of radial specific equipment and sheaths used in these studies that would increase RAS rates, particularly when using sheaths without hydrophilic coatings [37]. An additional factor is that many centers use smaller diameter 5Fr radial sheaths and catheters for diagnostic cardiac catheterization that would decrease rates of RAS observed as would use of more contemporary thinner wall sheaths such as the Glidesheath Slender which combines an inner diameter compatible with 6Fr guiding catheter with an outer diameter close to current 5Fr sheaths where RAS rates have been reported as low as 4.4% [38]. Finally sheathless guide catheter usage may also result in lower rates of RAS than those reported in the 'placebo'…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Another approach to this problem is offered by the 7‐Fr Glidesheath Slender (Terumo, Tokyo, Japan), a hydrophilic radial sheath that combines an inner diameter compatible with any 7‐Fr guiding catheter with an outer diameter close to current 6‐Fr sheaths. Experience with the 6‐Fr Glidesheath Slender is promising and clinical data on the 7‐Fr iteration is awaited.…”
Section: Pushing the Tra Indication Furthermentioning
confidence: 99%
“…The length of the 5Fr GSS is 16 cm. Aminian et al reported the safety and feasibility of the 6 Fr GSS [6]. In this study, initial experience with the 5 Fr GSS (4 Fr outer diameter) was evaluated in patients undergoing TRA and TRI, focusing on safety and feasibility.
Fig.
…”
Section: Introductionmentioning
confidence: 99%